Thames (Whaler) logbook - Thames (Whaler)
Five volume logbook (500 pages) kept by Nathan H. Cook on the whaler Thames with records on weather, course, whale sightings and captures, and events aboard ship. Port of embarkation was Sag Harbor, Long Island, N.Y. Places visited include Brazil, the Main Bank whaling grounds off the tip of South America, Patagonia, and Tristan da Cunha islands. Ship's masters were Huntting Cooper and David Hand, Jr.
Collection material in English.
Keywords: Cook, Nathan H. -- (Whaling master); Cooper, Huntting, -- 1792-; Hand, David, -- Jr; Marine meteorology -- Atlantic Ocean; Ports of entry -- New York (State); Ships' papers -- 19th century; Whalers (Persons); Whaling -- Brazil; Whaling -- New York (State) -- Sag Harbor; Whaling -- Patagonia (Argentina and Chile); Whaling -- South America; Whaling -- Tristan da Cunha